Non functional adrenocortical carcinoma (Faculty of Medicine Universitas Indonesia, 2008)
Adrenocortical carcinoma is a rare disease with an incidence of approximately 1-2 per million populations per year. The main symptoms are abdominal mass with or without endocrine dysfunction. However, there are difficulties in the diagnosis and treatment of this case due to its unspecific clinical presentation which sometimes require additional diagnostic methods such as immunohistochemistry. The prognosis is often poor, especially when it's impossible to resect the entire tumor. We present one case of adrenocortical carcinoma in RSCM which was diagnosed through immunohistochemistry examination postoperatively in patient with giant intra-abdominal tumor (mesenteric cyst). (Med J Indones 2008; 17: 203-9)